Integrating QR codes in a blended context-oriented mobile Learning model: a proposal - Amaral, Cristina (2018)
Technologies are creating learning opportunities that challenge traditional educational institutions. Students use mobile technologies outside the classroom but aren’t allowed to use them inside. Learning through mobile devices, known in literature as mobile learning (m-learning), highlights the acquisition of context-oriented contents. One of the promising technologies to be used for this goal is a variant of barcodes; quick response codes (QR-codes). In the suggested learning system, QR codes will allow an automatic authentication on moodle platform by the student through his profile and his mobile device. These codes enclose the necessary information to connect the context-oriented materials and the learning places. Each student follows guidelines with the instructions of the learning places to visit, informing about the QR codes to decrypt. The detected information is sent to the moodle platform asking for the context-oriented learning material. A case study will be conducted to show the degree of efficiency and effectiveness of its use and relevance in the teaching-learning process.